Super-mini percutaneous nephrolithotomy (PCNL) vs standard PCNL for the management of renal calculi of <2 cm: A randomised controlled study - Guddeti, Raja Sekhar; Hegde, Padmaraj; Chawla, Arun; de la Rosette, Jean J. M. C. H.; Pes, Maria Pilar Laguna; Kapadia, Aseem (Wiley, 2020)
Objective To compare the effectiveness and safety of standard percutaneous nephrolithotomy (sPCNL) and super-mini PCNL (SMP). Patients and Methods A total of 150 patients presenting with renal calculi of <2 cm were randomised to either sPCNL (Group 1) or SMP (Group 2). Randomisation was based on centralised computer-generated numbers. Variables studied included: stone-free rates (SFRs), operative time, intra- and postoperative complications, postoperative pain score, analgesic requirement, and hospital stay. Statistical analysis was performed using at-test or Mann-WhitneyU-test for continuous variables and chi-squared test or Fisher's exact test for categorical variables. Results Between September 2018 and April 2019, 75 patients were included in each group. The SFRs of the groups were similar (97.33 vs 98.66%,P= 0.56). The mean (sd)operative time was significantly longer in Group 2, at 36.40 (14.07) vs 23.12 (11.96) min (P< 0.001). The mean (sd)decrease in haemoglobin was significantly less in Group 2, at 3.0 (4.9) vs 7.5 (6.5) g/L (P< 0.001). The mean (sd)pain score at 24 h was significantly lower in Group 2, at 0.3 (0.46) vs 0.75 (0.53) (P< 0.001). The mean (sd)analgesic requirement was significantly less in Group 2, at 67 (22.49) vs 91.5 (30.56) mg tramadol (P< 0.001). The mean (sd) hospital stay was significantly less in Group 2, at 28.38 (3.6) vs 39.84 (3.7) h (P< 0.001). Conclusions SMP is equally as effective as sPCNL for managing renal calculi of <2 cm, with improved safety. Although SMP is associated with a longer operative time, it has a significantly lower incidence of bleeding and postoperative pain, and a shorter hospital stay.
Keywords: Percutaneous Nephrolithotomy; Renal Calculi; Stone-Free Rate; Morbidity; Complication